The effectiveness of e-learning in focused cardiac ultrasound training: a prospective controlled study - Ruppert, Johannes; Krüger, Rebecca; Göbel, Sebastian; Wolfhard, Susanna; Lorenz, LivAnnebritt; Weimer, Andreas; Kloeckner, Roman; Waezsada, Elias; Buggenhagen, Holger; WeinmannMenke, Julia; Weimer, Johannes Matthias (BMC medical education, 2025)
Introduction: Focused Cardiac Ultrasound (FOCUS) is an essential tool for rapid cardiac assessment across various clinical subspecialties. Consequently, teaching foundational FOCUS skills is of critical importance. This study investigates the effectiveness of e-learning in imparting FOCUS skills. Materials and methods: This prospective, controlled study assessed competency development among medical students attending a FOCUS workshop (study group) at two time points: T1 (pre-training) and T2 (post-training, after completing e-learning). The competence gain of the group was compared to a reference group (control group) of physicians who had also used the e-learning in preparation for a certified FOCUS workshop. Objective competencies were measured at both time points using short-answer and multiple-choice theory tests. Subjective self-assessments of competencies and opinions of the e-learning were investigated through evaluation forms at T2 using a 7-point Likert scale (1 = strongly disagree, 7 = strongly agree). Demographic information was collected at T1, and user behaviour during e-learning was assessed at T2. Primary endpoints were the increase in theoretical competencies (study group) and the comparison of subjective and objective competency levels (study vs. reference). Results: A total of 104 participants (study group = 48; reference group = 56) were included. The study group exhibited a significant (p < 0.001) increase in theoretical competencies. However, at T2 the reference group achieved significantly higher theoretical test scores (p < 0.001). One influencing factor was previous practical experience (p = 0.02), which was significantly higher in the reference group (p < 0.001). Both groups estimated their competency at the end of preparation to be at similar levels (4.3 ± 0.9 scalepoints [SP] versus 4.3 ± 1.0 SP; p = 0.94). Evaluation results of the e-learning were positive in both groups (5.8 ± 0.9 SP versus 6.2 ± 0.7 SP; p = 0.04), with results in the reference group being significantly higher. Conclusion: Both the improvement in competencies and the positive reception of digital learning media should encourage the increased implementation of e-learning formats. This study shows that such formats in ultrasound training can effectively complement face-to-face workshops and should be included in certified training curricula.